2009 Global Hunger Index: the challenge of hunger: Focus on financial crisis and gender inequality - von Grebmer, Klaus; Nestorova, Bella; Quisumbing, Agnes R.; Fertziger, Rebecca; Fritschel, Heidi; Pandya-Lorch, Rajul; Yohannes, Yisehac (Welthungerhilfe, 2009)
In 2009, high and volatile food prices combined with economic recession posed significant risks to poor and vulnerable households, with often dire consequences for their food security. The 2009 Global Hunger Index (GHI), the fourth in an annual series that records the state of hunger both worldwide and country by country, shows that the global economic downturn could make many countries even more vulnerable to hunger and that high rates of hunger are strongly linked to gender inequalities. Overall, limited progress has been made in reducing hunger since 1990.